Improvement of mead fermentation by honey‐must supplementation. Issue 3 (19th June 2015) - Pereira, Ana Paula; Mendes‐Ferreira, Ana; Estevinho, Leticia M.; Mendes‐Faia, Arlete
<x xml:space="preserve">Abstract</x> Through honey's fermentation, diverse beverages can be obtained, among which is mead, an alcoholic drink with 8 to 18% of ethanol (v/v). Since honey is a matrix with a low nutrient concentration and other unfavourable growth conditions, several problems are usually encountered, namely delayed or arrested fermentations, unsatisfactory quality parameters and lack of uniformity of the final product, as well as unpleasant sensory properties. In this context, the aim of this work was to optimize mead production through honey‐must supplementation with (a) salts, (b) vitamins or (c) salts + vitamins. The effects of the honey‐must formulation on the fermentation kinetics, growth profile and physicochemical characteristics of final meads were evaluated. The results showed minor differences in the fermentation profile and time between fermentations with the different formulations. The growth profile was influenced more by the yeast strain than by the supplements added to the honey‐must. In general, the honey‐must composition did not influence meads' final characteristics, except regarding the SO2 concentration of the meads produced using the strain QA23. In summary, the addition of salts and/or vitamins to honey‐must had no positive effects on the fermentation, growth profile or characteristics of the final products. Copyright © 2015 The Institute of Brewing & Distilling